Uniocular high myopia: A case series - Sareen, Arti; Sharma, Mukta; Negi, Sunder Singh (Indian Journal of Case Reports, 2019)
Anisometropic myopia is a rare and unique entity in which the two eyes of the same individual have grown unequally. This poses the risk of amblyopia in the more myopic eye if not detected and corrected early in life. Here, we present a case series of four cases of uniocular amblyopia. In all the four cases, there was a disparity in axial length of the two eyes. The other parameters including keratometry readings were normal in all the cases. This led to uniocular myopia. The anisometropic amblyopia hence caused led to a decrease of vision in the concerned eyes. This unilateral amblyopia caused could have been easily prevented if the timely diagnosis had been made and treatment instituted early in life.